The transient receptor potential type vanilloid 1 suppresses skin carcinogenesis - Bode, Ann M. (2009)
Blockade of the transient receptor potential channel vanilloid subfamily 1 (TRPV1) is suggested as a therapeutic approach to pain relief. However, TRPV1 is a widely expressed protein whose function might be critical in various non-neuronal physiological conditions. The epidermal growth factor receptor (EGFR) is a receptor tyrosine kinase that is overexpressed in many human epithelial cancers and is a potential target for anticancer drugs. Here we show that TRPV1 interacts with the EGFR leading to EGFR degradation. Notably, the absence of TRPV1 in mice results in a striking increase in skin carcinogenesis. The TRPV1 is the first membrane receptor shown to have a tumor-suppressing effect associated with the downregulation of another membrane receptor. The data suggest that even though a great deal of interest has focused on the TRPV1 as a target for pain relief, the chronic blockade of this pain receptor might increase the risk for cancer development.